TINGKAT PENGETAHUAN PASIEN TENTANG KEGUNAAN GIGI DENGAN MINAT MENGGUNAKAN GIGI TIRUAN SEBAGIAN LEPASAN DI KLINIK - Domingos Pinto; Siti Sulastri; Siti Hidayati (Journal of Oral Health Care, 2014)
Background : Knowledge is the result of human sensing,or know someone on the outcome of certain objectsthrough the senses of its senses vision, sense of hearing,smell, taste and touch. Most of the knowledge gainedthrough the senses of a person’s vision and sense ofhearing. Based on a preliminary study conducted by interviewingpeople in 5 patients in the clinic after tooth extractionDental Center dated 20 July 2013 stating that thepatient’s teeth without food mastication process, appearanceand function of a person’s speech will be interrupted.Objective: To determine the relationship between patients’knowledge about the usefulness of the teeth with an interestin using removable partial dentures on patientsin theclinic Dental Center.Research methods : cross-sectional research design.Sampling using simple techniques Purporsivesampling.A large sample of 30 people. The research hypothesis isno association between tinggkat knowledge with interestusing a removable partial denture clinic Dental Center,Yogyakarta.Results: Statistical test results obtained Chi - Square p =0.122 > 0.05 so that Ho accepted and Ha is rejected meaningthere is no meaningful relationship.Conclusion : In patients who have a high level of knowledgeabout the usefulness of denture teeth tend to use asa replacement for natural tooth function and appearancereasons.